2022
DOI: 10.1186/s12884-022-04773-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a tele-educational intervention on modifying dysfunctional sexual beliefs of pregnant women: a randomized controlled trial

Abstract: Background & aim Some cultural scenarios in pregnancy and childbirth reinforce dysfunctional sexual beliefs that reverse changes in the couple's sexual life. The present study aimed to investigate the effect of education by sending text messages on modifying dysfunctional sexual beliefs in pregnant women. Methods & materials This study is a randomized clinical trial, and 82 eligible pregnant women referred to educational-medical centers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Participants are included in the interventional group and the control group. We have five groups of telehealth: mobile health (17,22), telemedicine (20,21), mobile applications (24), tele-educational (26), and mobile phones (18,19), Telehealth was developed before the COVID-2019 pandemic, but its use has not been as widespread as during the COVID-2019 pandemic. Telehealth has grown all over the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants are included in the interventional group and the control group. We have five groups of telehealth: mobile health (17,22), telemedicine (20,21), mobile applications (24), tele-educational (26), and mobile phones (18,19), Telehealth was developed before the COVID-2019 pandemic, but its use has not been as widespread as during the COVID-2019 pandemic. Telehealth has grown all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers develop telehealth integrated with the hospital with the goal of facilitating the participant's consultation with a specialist or subspecialist (20). Other studies have shown that intellectual messages can increase the sexual confidence of pregnant women in the second trimester (26). Researchers develop tele-education to overcome sexual problems during pregnancy.…”
Section: No Authormentioning
confidence: 99%
See 1 more Smart Citation